2010
DOI: 10.1103/physrevlett.105.135702
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Hierarchy of Relaxation Events, Dynamical Heterogeneities, and Structural Reorganization in a Supercooled Liquid

Abstract: We identify the pattern of microscopic dynamical relaxation for a two-dimensional glass-forming liquid. On short time scales, bursts of irreversible particle motion, called cage jumps, aggregate into clusters. On larger time scales, clusters aggregate both spatially and temporally into avalanches. This propagation of mobility takes place along the soft regions of the systems, which have been identified by computing isoconfigurational Debye-Waller maps. Our results characterize the way in which dynamical hetero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(183 citation statements)
references
References 21 publications
14
167
2
Order By: Relevance
“…In disordered solids, it has long been hypothesized that localized particle rearrangements [3] induced by stress or temperature also occur at localized flow defects [4][5][6]. Like dislocations in crystals [7], flow defects in disordered solids are particularly effective in scattering sound waves, so analyses of the low-frequency vibrational modes [8] have been used successfully to demonstrate the existence of localized flow defects [7,[9][10][11][12][13][14][15][16][17]. However, all attempts to identify flow defects [18,19] directly from the structure, without using knowledge of the interparticle interactions, have failed [18,19].…”
mentioning
confidence: 99%
“…In disordered solids, it has long been hypothesized that localized particle rearrangements [3] induced by stress or temperature also occur at localized flow defects [4][5][6]. Like dislocations in crystals [7], flow defects in disordered solids are particularly effective in scattering sound waves, so analyses of the low-frequency vibrational modes [8] have been used successfully to demonstrate the existence of localized flow defects [7,[9][10][11][12][13][14][15][16][17]. However, all attempts to identify flow defects [18,19] directly from the structure, without using knowledge of the interparticle interactions, have failed [18,19].…”
mentioning
confidence: 99%
“…[25][26][27] Later it was demonstrated that the real space properties of the inherent structure normal modes correlate closely with dynamical heterogeneities and irreversible configurational rearrangements. [28][29][30][31] Such connections have also been demonstrated in experiments performed on colloidal suspensions. [32][33][34][35] It remains unclear in the examples discussed above if the harmonic soft modes are an active player in the dynamics or if they are spectators whose positions correlate with regions of dynamical activity but which do not influence particle relaxation.…”
Section: Introductionmentioning
confidence: 64%
“…Once the timescales are properly rescaled, the similarities with the granular media experiments are astonishing [34,48].…”
Section: Spatio-temporal Organization Of the Relaxation Close To The mentioning
confidence: 99%
“…In the first section, we describe the microscopic mechanisms at play in granular systems approaching the glass transition and emphasize the decreasing role of facilitation associated to the emergence of large-scale dynamical heterogeneities [34,35,36]. In the second section, we experimentally study the vicinity of the Jamming transition by investigating both statics and dynamics of the contact network in a horizontally shaken bi-disperse packing of brass or photo-elastic discs.…”
Section: Introductionmentioning
confidence: 99%